Global warming trends [electronic resource] : ecological footprints - Casper, Julie Kerr (New York, NY : Facts on File, 2009)
Provides an introduction to global warming that explains why and how it occurs and the accuracy and inaccuracy of the media type that accompanies it
Description based on print version record
Includes bibliographical references and index
Keywords: Global warming; Paleoclimatology